2019
DOI: 10.3390/app9183767
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Properties of Rock-Filled Concrete

Abstract: In order to comprehensively evaluate the properties of rock-filled concrete (RFC) with the strength of C15, lab experimental test and in-situ test are applied to explore the mechanical, hydraulic, ultrasonic characteristics of RFC in Hantang reservoir dam. Four types of defects within RFC are shown from the appearance of borehole cores specimens: (1) large sized voids existing in interfacial transition zone (ITZ) between self-compacting concrete (SCC) and rock block (RB); (2) bad cohesion in ITZ; (3) joints wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As depicted in Figure 2, SCC is produced on-site at a batching plant and transported to the designated area using concrete mixers. It is advisable to provide a curing period of 14 days for each RFC casting layer, with a recommended thickness range of 1.8-2.0 m. It is imperative to strictly adhere to the regulations outlined in the "Occupational Safety and Health Design Law for Water Resources and Hydropower Projects (GB 50706-2011)" as mandated by the Ministry of Water Resources of the People's Republic of China in 2012 during the dam-building process [23]. Various experiments have been undertaken, encompassing evaluations of HSCC in terms of its capacity to fill gaps between rocks, compressive strength, and permeability [24].…”
Section: Rock-filled Concrete Constructionmentioning
confidence: 99%
“…As depicted in Figure 2, SCC is produced on-site at a batching plant and transported to the designated area using concrete mixers. It is advisable to provide a curing period of 14 days for each RFC casting layer, with a recommended thickness range of 1.8-2.0 m. It is imperative to strictly adhere to the regulations outlined in the "Occupational Safety and Health Design Law for Water Resources and Hydropower Projects (GB 50706-2011)" as mandated by the Ministry of Water Resources of the People's Republic of China in 2012 during the dam-building process [23]. Various experiments have been undertaken, encompassing evaluations of HSCC in terms of its capacity to fill gaps between rocks, compressive strength, and permeability [24].…”
Section: Rock-filled Concrete Constructionmentioning
confidence: 99%
“…He et al [7] conducted compression creep and shrinkage tests on RFC and SCC, revealing that the creep and shrinkage strains of RFC were lower than those of SCC; additionally, they found that rock aggregates had a significant impact on the creep behavior of RFC. Wei et al [8] tested the mechanical properties of RFC specimens by coring the borehole of the dam, which showed that the average compressive strength of RFC was slightly greater than the SCC strength, but much less than the rock strength. Li et al [9] conducted uniaxial compression tests on 39 RFC cube cutting specimens; these cutting specimens were taken from a large volume test block cast in situ using the same material, process, and environment as the construction site.…”
Section: Introductionmentioning
confidence: 99%